2014
DOI: 10.3906/vet-1307-47
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among oocyte quality, hepatic triacylglycerols, and some blood metabolites in Carora breed cows during early postpartum

Abstract: The aim of this study was to assess the relationships of hepatic triacylglycerol (TAG), plasma glucose, plasma cholesterol, and plasma urea nitrogen (PUN) concentrations with the morphological quality of oocytes obtained from 20 Carora breed lactating cows at days 20 and 35 postpartum in a commercial farm. Oocytes were obtained through the technique of transvaginal ultrasound-guided follicle aspiration. Change in body condition score (0.35 vs. 0.44, P = 0.02) and mean plasma cholesterol (3.59 vs. 4.35 mmol/L, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…A positive correlation (r=0.41) was reported by Rodriguez et al . [ 30 ] between the level of cholesterol and oocyte yield. Garnsworthy et al .…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation (r=0.41) was reported by Rodriguez et al . [ 30 ] between the level of cholesterol and oocyte yield. Garnsworthy et al .…”
Section: Discussionmentioning
confidence: 99%
“…This study presents a significant increase of the level of urea and cholesterol with BCS = 3. Rodriguez et al [50] showed a positive correlation between the level of cholesterol and oocyte yield, suggesting that energy balance and BCS play an important role in reproductive function and especially on ovarian level.…”
mentioning
confidence: 99%